ANALISIS AKTA JUAL BELI TANAH YANG DIBUAT TANPA PERSETUJUAN PEMILIK TANAH DALAM PERSPEKTIF PERATURAN PEMERINTAH REPUBLIK IINDONESIA NOMOR 24 TAHUN 2016 TERKAIT PERATURAN JABATAN PEJABAT PEMBUAT AKTA TANAH (STUDI KASUS PUTUSAN NOMOR 347/PDT/2017/.PN.JKT.TIM) - Faishal Nurachmad; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2020)
Along with the rate of growth and development of such a large population, and the area of land is relatively not increased, the soil has significance in human life because the land has a dual function, namely as a social asset and as a capital asset, this causes the need for land is increasing, thus causing various potential conflicts or disputes in the right to purchase land. Land Acquisition Officer (PPAT) is a public official authorized to make authentic deeds concerning certain legal acts concerning land rights or ownership of apartment units, based on Government Regulation No. 24 of 2016 on PPAT in practice often the making of Deed of Sale and Purchase of land which is inconsistent with legal corridor which can cause risks for certainty of land rights. In this case, PPAT is asked to be a juridical account in relation to the authentic deed which it contains contains legal defects. The problem that becomes the discussion in this research is how the responsibility of PPAT in making the Deed of Sale and Purchase of the land and the result of the law it made if it contains legal defect.